A crucial temporal accuracy test of combining EEG and Tobii eye tracker. Issue 13 (March 2017) - Xue, Jiguo; Quan, Cheng; Li, Chunyong; Yue, Jingwei; Zhang, Chenggang
Abstract : Abstract: Eye tracking and event-related potentials have been widely used in the field of cognitive psychology and neuroscience. Both techniques have the ability to refine cognitive models through a precise timeline description; nevertheless, they also have severe limitations. Combining measures of event-related potentials and eye movements can contribute to cognitive process capture, which provides the possibility to determine precisely when and in which order different cognitive operations occur. Combining of event-related potentials and eye movements has been recently conducted by synchronizing measures from an infrared eye tracker with an electroencephalograph to allow simultaneous data recording. Here, we describe in detail 4 types of co-registration methods for event-related potentials and eye movements on the Tobii platform. Moreover, the present investigation was designed to evaluate the temporal accuracy of data obtained using the 4 methods. We found that the method based on the Tobii Pro Analytics software development kit had a higher degree of temporal accuracy than the other co-registration methods. Furthermore, the reasons for the different temporal accuracies were assessed, and potential measures to correct clock drift were taken. General suggestions are made regarding timing in the co-registration of the electroencephalograph and eye tracker. Abstract : Supplemental Digital Content is available in the text